Hurricanes threaten species and alter evolutionary trajectories on tropical islands - Dalsgaard, Bo; Temeles, Ethan J. (Current biology, 2024)
Hurricanes are natural phenomena, but anthropogenic climate change will cause hurricanes to be stronger and more frequent in the future. It has long been known that hurricanes impact plants and animals, but only recently has the impact on biodiversity been mapped globally, showing that species at risk of extinction due to hurricanes are largely restricted to tropical islands. Tropical islands harbor many plants and animals found nowhere else, many of which are currently threatened, and tropical islands have already suffered a disproportionate number of species extinctions due to human activity and introductions of non-native species. The big question is whether species on tropical islands are adapted to hurricane disturbance and will be able to cope with stronger and more frequent storms, or whether tropical islands will see a wave of hurricane-induced extinctions in the future. Here, we discuss this question and how hurricanes will reshuffle interactions between species — such as those between nectarivorous birds and their flowers — and will alter evolutionary trajectories for coadapted species. Moreover, we discuss the role of life history and other taxa-specific traits, such as diet preferences and dispersal ability, both to survive the direct and indirect impact of hurricanes and to recolonize islands when local populations have been eliminated. We also highlight how topographic complexity and island area may buffer against hurricanes; thus, biodiversity on small and low-lying islands should be more impacted than biodiversity on large and mountainous islands. We end by discussing conservation efforts to diminish the detrimental ecological and evolutionary effects of stronger and more frequent hurricanes on tropical islands. Dalsgaard and Temeles discuss the potential of hurricanes to pose a greater threat to island species and their evolution.